Impact of gut microbiota on immune reactions relevant to lung pathologies - Popović, Dušanka; Malešević, Anastasija; Tucović, Dina; Kulaš, Jelena; Popov Aleksandrov, Aleksandra; Mirkov, Ivana (Archives of Pharmacy, 2023)
Bacterial microbiota of the gastrointestinal tract is known to prevent the invasion of pathogenic microorganisms and regulate intestinal permeability, digestion, metabolism, and immune response. It affects function, homeostasis, and disease outcomes in the gastrointestinal tract and extra-intestinal sites such as the lungs. This review summarizes the currently available knowledge regarding the gut-lung axis. The association of bacterial composition and/or dysbiosis in the gut with asthma, chronic obstructive lung disease, cystic fibrosis, recurrent respiratory tract infections, and lung cancer in humans is highlighted, as well as data obtained from animal models of pulmonary inflammation, which indicated that modulation of immune system activity lies at the base of this interaction. Additionally, the potential use of prebiotics, probiotics, and postbiotics in the treatment of lung inflammation is presented.
Keywords: gut bacterial microbiota; gut-lung axis; lung inflammation